Genetic susceptibility to dermatophyte infections: a review - Luh Gede Melia Puspita Sari Puspita Sari; I Gusti Ayu Agung Dwi Karmila; Putu Ayu Yunita Primasari (Explorer Front, 2026)
Dermatophytes infect people of all ages, races, genders, and socioeconomic statuses. However, some groups of individuals tend to be more susceptible. Several risk factors have been described, particularly in immunocompromised individuals and patients with severe illnesses. Unfortunately, this still does not explain why only some immunocompetent individuals experience infections. Some studies have concluded that genetic susceptibility is associated with defects in Toll-like receptors involved in the inflammatory response and pathogen clearance mechanisms, C-type lectin receptors, nucleotide-binding and oligomerization domain (NOD)-like receptors, and defects in soluble pattern recognition receptors, which can lead to impaired phagocytosis and pathogen elimination by neutrophils. The purpose of this article is to highlight how the human body reacts to fungal exposure and a number of genetic changes that may be the cause of fungal infections, even in immunocompetent people.